2009
DOI: 10.1209/0295-5075/87/55002
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale physics mechanisms and spontaneous edge transport bifurcations in fusion plasmas

Abstract: The magnitude of radial transport in magnetic confinement devices for controlled nuclear fusion suffers spontaneous bifurcations when specific system parameter values are exceeded. Here we show, for the first time, that the correlation length of the plasma potential becomes of the order of the machine size during the edge bifurcation itself, quite unlike the density fluctuations. The mechanism governing the development of this bifurcation, leading to the establishment of an edge transport barrier, is still one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 27 publications
21
48
0
Order By: Relevance
“…Another result has been reported from the JFT-2M tokamak [7], in which both plus and minus phase delay (∝ ) of GAMs were seen in different radial locations, suggesting a non-uniform propagation of GAMs in both outward and inward directions. In the TJ-II stellarator, a sign of radially propagating zonal flows (below 20 kHz) has also been mentioned [19]. In addition to above results, our observations provide direct and explicit evidence on the GAM propagation, which could be one of important characteristics of the GAM zonal flows.…”
Section: Properties Of Gam Zonal Flowssupporting
confidence: 79%
See 1 more Smart Citation
“…Another result has been reported from the JFT-2M tokamak [7], in which both plus and minus phase delay (∝ ) of GAMs were seen in different radial locations, suggesting a non-uniform propagation of GAMs in both outward and inward directions. In the TJ-II stellarator, a sign of radially propagating zonal flows (below 20 kHz) has also been mentioned [19]. In addition to above results, our observations provide direct and explicit evidence on the GAM propagation, which could be one of important characteristics of the GAM zonal flows.…”
Section: Properties Of Gam Zonal Flowssupporting
confidence: 79%
“…Only in the HL-2A tokamak the statistical analysis of the radial wavenumber spectrum gives hints that the GAM packet propagates in radially outward direction with approximately the same group and phase velocity [11]. In the JFT-2M tokamak and TJ-II stellarator a sign of radially propagating GAMs or zonal flows (below 20 kHz) has also been commented [7,19].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [22], it was shown that LRCs in TJ-II emerge in the vicinity of this value (where the mean electric field changes from a positive to a negative root) and at high densities (∼ 2×10 19 m −3 ) close to the L-H transition. The investigation of the spatio-temporal characteristics of the correlated structures at high density is left to future work.…”
Section: Global Modulations Of Floating Potential Profile and Zf Dynamentioning
confidence: 85%
“…The time evolution of both, E r shear and density fluctuations, indicates that the reduction in density fluctuations precedes the increase in the mean E r shear but is simultaneous with the increase in the low frequency oscillating sheared flow [35]. These observations, together with the amplification of long-range correlations in the potential fluctuations [36], are consistent with L-H transition models predicting plasma bifurcations triggered by ZFs [10,11]. Further experimental evidence supporting the central role of ZFs has been recently observed in experiments carried out close to the transition threshold conditions: a coupling between flows and turbulence is measured which reveals a characteristic predator-prey behaviour [37].…”
Section: Introductionmentioning
confidence: 81%